Effects of an entire season on physical fitness changes in elite male handball - Gorostiaga, E. M.; Granados, C.; Ibanez, J.; Gonzalez-Badillo, J. J.; Izquierdo, M. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Fifteen elite male handball players were studied to examine the effects of an entire season of play on physical fitness and throwing velocity.